SELF-CONFIDENCE OF 5-6 YEAR-OLD CHILDREN REVIEWED FROM PERMISSIVE AND AUTHORITARY PARENTING PATTERNS - Nadhifah, Vita; Hasiana, Isabella (As-Sulthan Journal of Education, 2024)
This study utilizes qualitative methods to explore the impacts of permissive and authoritarian parenting styles on the self-confidence of 5-6-year-old children. Self-confidence is crucial to develop from early childhood due to its long-term effects on their subsequent growth. One significant outcome is that children become more capable of facing challenges and difficult situations. The subjects of this research are children aged 5-6 years raised under permissive and authoritarian parental styles. Data collection methods include observations and interviews, with data analysis conducted using the Miles and Huberman model. The findings reveal that parents employing permissive parenting styles tend to create environments conducive to exploration and bolstering their children's self-confidence. In contrast, parents using authoritarian parenting styles tend to raise children who are less confident, feeling constrained by strict rules. The implications of these findings underscore the need for more responsive and supportive parenting approaches to aid positive self-confidence development in early childhood.